2021
DOI: 10.1177/15353702211019697
|View full text |Cite
|
Sign up to set email alerts
|

Role of sex hormones in lung cancer

Abstract: Lung cancer represents the world’s leading cause of cancer deaths. Sex differences in the incidence and mortality rates for various types of lung cancers have been identified, but the biological and endocrine mechanisms implicated in these disparities have not yet been determined. While some cancers such as lung adenocarcinoma are more commonly found among women than men, others like squamous cell carcinoma display the opposite pattern or show no sex differences. Associations of tobacco product use rates, susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 154 publications
(181 reference statements)
0
21
0
2
Order By: Relevance
“…In other hand the result appear that NSCLC more than SCLC this agree with (Scagliotti et al, 2022) observed that non-small cell lung cancer (NSCLC) accounts for ∼ 85% of all lung cancers and has multiple histological subtypes including adenocarcinoma and central squamous cell carcinoma. Also , (Fuentes et al, 2021) confirmed that small cell carcinoma accounts for about 20% of cases while non-small cell carcinoma comprises 80% of lung malignancy. Also (Schabath & Cote, 2019) they found NSCLC represents more than 80 -85% of lung cancers of lung cancers of which approximately 40% are adenocarcinoma, 25% to 30% are squamous cell carcinoma, and 10% to 15% are large cell carcinomas.…”
Section: Demographic Characteristics For 150 Patientsmentioning
confidence: 67%
“…In other hand the result appear that NSCLC more than SCLC this agree with (Scagliotti et al, 2022) observed that non-small cell lung cancer (NSCLC) accounts for ∼ 85% of all lung cancers and has multiple histological subtypes including adenocarcinoma and central squamous cell carcinoma. Also , (Fuentes et al, 2021) confirmed that small cell carcinoma accounts for about 20% of cases while non-small cell carcinoma comprises 80% of lung malignancy. Also (Schabath & Cote, 2019) they found NSCLC represents more than 80 -85% of lung cancers of lung cancers of which approximately 40% are adenocarcinoma, 25% to 30% are squamous cell carcinoma, and 10% to 15% are large cell carcinomas.…”
Section: Demographic Characteristics For 150 Patientsmentioning
confidence: 67%
“…Various lines of evidence implicate androgen receptor signaling to lung cancer biology. The proposed mechanism is based on the androgen's receptor induction of cyclin D1 expression, macrophage M2 polarization and direct effect on lung cancer growth [24]. Preclinical studies using lung cancer cell lines showed strong expression of androgen receptors, while treatment of a lung adenocarcinoma cell line with androgen led to a downregulation of genes involved in cellular respiration [16,25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of estrogen plus progestin was associated with a statistically significant hazard ratio of death from lung cancer in the WHI trials 45 . Furthermore, women who smoke are at greater risk than men who smoke, and an estrogen by smoking interaction has been hypothesized to explain this trend 42, 46 . Finally, observational analyses of population cancer datasets have found that anti-estrogen therapies improve lung cancer-specific survival among subjects with lung cancer in the presence or absence of prior history of breast cancer 47, 48 .…”
Section: Discussionmentioning
confidence: 99%